Quality vs. Quantity in Information Transmission: Theory and Experimental Evidence - Jonathan Lafky; Alistair J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2015)
Information sharing has become increasingly important in helping consumers make better, more informed choices over competing products. Our project uses a novel theoretical framework and laboratory experiments to analyze three simple, commonly used incentive schemes against an unincentivized baseline. Each incentive scheme has qualitatively different theoretical predictions for behavior and efficiency, while our laboratory experiments examine the degree to which these differences manifest themselves, and the best-cast theory's robustness to human behavior. Our findings indicate the possibility for substantial efficiency gains by introducing incentives that reward information sharing, even where those incentives drive a wedge between those sending and those receiving information. In particular, our results point to a misaligned incentive commonly found in the field, sales commissions, as being a robust institution to stimulate the exchange of information.
Keywords: C92; D02; D83; 330; rating incentives; institutional stability; social information